A Peek into the US Informal STEM Landscape through Theconnectory.org. Issue 1 (13th October 2021) - Deimen, Sebastian; Cui, Hong; Higgins, Michelle
Abstract: It's well‐known that informal STEM learning is a critical component of STEM education. However, there is not a comprehensive directory, at the state or national level, listing informal STEM programs offered in the US. This makes it difficult to assess the national landscape of informal STEM programs. Theconnectory.org is by far the most comprehensive listing that aims to connect learners and volunteers to informal STEM learning opportunities. In this poster, we present the results from a data analytics project using the informal STEM program information collected through theconnectory.org API to sketch a preliminary picture of what kind of programs are offered and what audiences are targeted. Theconnectory.org has the potential to become a primary resource for STEM learners, educators, and policymakers. There are ways the ASIST community (faculty and students) can help enrich this resource.